Development of a Dual-Targeted Oral Delivery System for Mesalazine and Acetaminophen - Fatemeh Soltani; Reihaneh Arghand; Ghazaleh Mehdipour; Hossein Shahdadi Sardou; Ali Mohammadi; Abbas Akhgari (Journal of Mazandaran University of Medical Sciences)
Background and purpose: Inflammatory bowel diseases (IBD) are chronic and recurrent inflammatory disorders of the gastrointestinal tract, classified into two main categories: ulcerative colitis and Crohn's disease. Mesalazine is the most commonly prescribed drug for the treatment of inflammatory bowel disease (IBD); however, its rapid absorption in the small intestine reduces its local effects in the colon. The use of mesalazine in coated pellet form as a multi-unit drug delivery system may enhance its effectiveness compared to conventional pharmaceutical forms such as tablets. Arthritis is one of the extra-intestinal manifestations of IBD, which can be alleviated by acetaminophen. The aim of this study is to design a multi-unit oral drug delivery system (pellets) that simultaneously delivers mesalazine to the large intestine and acetaminophen to the stomach. Materials and methods: In this experimental study, mesalazine pellets were prepared using the extrusion-spheronization method and coated with pH-dependent polymers (Eudragit® L100 and Eudragit® S100) as well as a combination of time-dependent (Eudragit® RS) and pH-dependent polymers (Eudragit® L100). Drug release was evaluated in simulated gastrointestinal environments, and the optimal formulations were identified. Subsequently, acetaminophen was loaded onto the optimized pellets using a fluid bed coater. The drug release profile was assessed using a continuous dissolution testing method. Thermal analysis, infrared spectroscopy, mechanical testing and scanning electron microscopy were performed to evaluate the physicochemical properties and investigate potential interactions. Results: Pellets coated with 40% Eudragit® RS and 60% Eudragit® L100, as well as those coated with 100% Eudragit® S100, were found to be more suitable for colon drug delivery than other formulations. Continuous dissolution testing showed that acetaminophen was released in a pH 1.2 environment within 2 hours, while mesalazine remained intact and reached the large intestine. Physicochemical tests indicated that the pellets had a smooth surface, uniform coating, and appropriate hardness, with no detectable interactions between the drugs and excipients. Conclusion: This study demonstrated that the optimized formulation effectively enables the targeted delivery of acetaminophen to the stomach and mesalazine to the colon in a single dosage form.